Pengaruh Dukungan Sosial Terhadap Kecemasan Pada Ibu Hamil di Puskesmas Jetis Kabupaten Ponorogo - Ambika Kurnia Mustikawati (Jurnal Delima Harapan, 2018)
Background: Pregnancy is a valuable thing, but also one of the great stresses for a woman both physically and mentally. Pregnant women with high anxiety will increase the risk of hypertension, difficulty sleeping and stroke, seizures and even death in the mother and fetus. In Puskesmas Ponorogo district the number of pregnant women as much as 5903 mothers, while in health centers Jetis the number of pregnant women as many as 200 mothers. Interview results, 21 out of 27 mothers said were very anxious during her pregnancy. The purpose of this study was to analyze the factors of social support for anxiety in pregnant women. Subjects and Methods: The type of research is analytical with cross-sectional approach. The location of research at Jetis health center Ponorogo regency. Research conducted on September 1 to October 15, 2016. Sample of 30 pregnant women using proportional random sampling technique. Dependent variable is anxiety, while independent variable is social support. Data collection techniques using questionnaires. Data analysis using Spearman's Rho using SPSS 18.0 for windows computer program. Results: The results showed that from 40 respondents, almost half were 13 (32.5%) multiparous had mild anxiety and nearly half were 13 (32.5%) primipara experienced moderate anxiety. of the 40 respondents, nearly half (12%) of 3 trimester pregnant women had moderate anxiety and a small proportion of 9 (22.5%) of 2 trimester pregnant women had mild anxiety. The result of calculation using spearman's rho statistic test obtained p = 0,006 <α 0,05 mean there is influence between parity with anxiety in pregnant woman with correlation coefficient of -0,424 which show intensity of influence of medium that is if the smaller parity hence more anxiety level. The calculation of gestational age with spearman's rho p = 0,023 <α 0.05 means that there is an influence between parity with anxiety in pregnant women with a correlation coefficient of 0.359 which shows the weakness of weak influence. Conclusion: The social support provided by husband and family will affect the level of anxiety in each pregnant woman. It is hoped for a place of research to provide a solution for pregnant women who experience anxiety so that pregnancy can run smoothly and respondents are expected to have a good coping mechanism in the face of anxiety for health and also the fetus.